22nd AIAA Computational Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-3067
|View full text |Cite
|
Sign up to set email alerts
|

RANS Simulations of a Channel Flow with a New Velocity/Pressure-Gradient Model

Abstract: Accurate prediction of wall-bounded flows with Reynolds-averaged Navier-Stokes turbulence models requires the improved modeling of physical processes that occur in turbulent flows such as the interaction of turbulent velocity and pressure fields, turbulent diffusion, and dissipative processes. Recently, novel models for the velocity/pressuregradient correlations through the fourth order were proposed by the authors and successfully validated against direct numerical simulation (DNS) data in wall-bounded flows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A new approach to quantifying uncertainty in DNS statistics that utilizes the self-consistency of RANS equations was developed in our group 6,7 . In this approach computed statistics from DNS are used to solve the RANS equations, and their solutions are compared back with the DNS data for velocity moments.…”
Section: Introductionmentioning
confidence: 99%
“…A new approach to quantifying uncertainty in DNS statistics that utilizes the self-consistency of RANS equations was developed in our group 6,7 . In this approach computed statistics from DNS are used to solve the RANS equations, and their solutions are compared back with the DNS data for velocity moments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to tackle model-form uncertainty include calibrations of a modified eddy viscosity field [9], the introduction of statistical error terms in the calibration procedure [2,10] or in the model transport equations [11], and the use of a stochastic counterpart of the Reynolds stress tensor [12]. Even UQ techniques for the RANS equations with no modelling, where the transport terms are represented with direct numerical simulation data, have been developed [13,14]. All these methods rely on detailed data from direct numerical simulations to infer about stochastic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Further, even if individual terms in the closure equations are modeled accurately, small discrepancies can lead to poor results. For instance, Poroseva and Murman 10 observed that even if some terms in a second moment closure are extracted directly from DNS, the overall prediction was not satisfactory. It is thus the balance between every term in the model equation that is important.…”
Section: Introductionmentioning
confidence: 99%